Jangan Khawatir: Sebuah Tinjauan Teologis Providensia Allah Menurut Lukas 12:22–32 - Sri Devita Br Hutasoit; Ratna Saragih; Berton Silaban (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Believers, both in the time of Jesus and in today’s context, live in situations shaped by social, political, economic, religious, and cultural influences that often give rise to anxiety and doubt about God’s providence. In Luke 12:22–32, Jesus delivers a teaching that prohibits worry and calls His followers to direct their hearts toward the Kingdom of God. For those living under Roman rule, these words were a source of comfort and encouragement to remain steadfast in their faith in God’s power, and for believers today, the same message continues to be relevant as guidance for managing worry with trust and hope. This study seeks to analyze Luke 12:22–32 from the perspective of the theology of God’s providence and to explain its implications for contemporary Christian life. The findings emphasize three key points: first, the passage affirms God as a sovereign, loving Father who cares deeply for His people; second, God’s providence includes both physical and spiritual needs, thus framing faith as an active trust that combines prayer, hope, and concrete action; and third, reflection on God’s providence strengthens believers to face modern anxieties by prioritizing the Kingdom of God, practicing spiritual discipline, and embodying solidarity with others. Although limited in scope as a textual study without cultural or empirical application, this research contributes significantly to understanding God’s providence in Luke 12:22–32 and underlines its relevance for addressing contemporary challenges while encouraging Christians to live out their faith in tangible ways.